Optimization Strategy For Inventory to Reduce Storage Costs of PT. Kelapa Sari, Batu City - Yovita Jelita; Gunawan, Cakti Indra; Warter Agustim (International Journal of Management and Business, 2025)
Inventory is a matter that plays a vital role for a company, especially in the manufacturing industry. Reasonable inventory control is necessary to manage inventory effectively and efficiently. This research was conducted at PT. Kelapa Sari. Primary data was obtained through observations in the warehouse, and interviews with relevant departments, and secondary data was obtained from company documents. The EOQ method aims to achieve minimal inventory levels, low costs, and better quality. Planning the EOQ method in the company can reduce the occurrence of stockouts, thereby not disrupting processes within the company and saving raw material inventory costs through the inventory efficiency implemented within the company. In addition, applying the EOQ method can reduce storage costs and save space, both for the warehouse and workspace. This method can also address issues arising from excessive inventory accumulation, thereby reducing the risks from stored inventory in the warehouse, such as soybeans that are susceptible to humidity or water. This EOQ analysis is easy and practical for planning how often a material should be purchased and in what quantities